4-Nerolidylcatechol: apoptosis by mitochondrial mechanisms with reduction in cyclin D1 at G0/G1 stage of the chronic myelogenous K562 cell line - Polyana Lopes Benfica; Renato Ivan de Ávila; Bruna dos Santos Rodrigues; Alane Pereira Cortez; Aline Carvalho Batista; Marilisa Pedroso Nogueira Gaeti; Eliana Martins Lima; Kênnia Rocha Rezende; Marize Campos Valadares (Taylor & Francis Group, 2017)
Context: 4-Nerolidylcatechol (4-NRC) has showed antitumor potential through apoptosis. However, its apoptotic mechanisms are still unclear, especially in leukemic cells. Objectives: To evaluate the cytotoxic potential of 4-NRC and its cell death pathways in p53-null K562 leukemic cells. Materials and methods: Cytotoxicity of 4-NRC (4.17-534.5 μM) over 24 h of exposure was evaluated by MTT assay. 4-NRC-induced apoptosis in K562 cells was investigated by phosphatidylserine (PS) externalization, cell cycle, sub-G1, mitochondrial evaluation, cytochrome c, cyclin D1 and intracellular reactive oxygen species (ROS) levels, and caspase activity analysis. Results: IC50 values obtained were 11.40, 27.31, 15.93 and 15.70 μM for lymphocytes, K562, HL-60 and Jurkat cells, respectively. In K562 cells, 4-NRC (27 μM) promoted apoptosis as verified by cellular morphological changes, a significant increase in PS externalization and sub-G1 cells. Moreover, it significantly arrested the cells at the G0/G1 phase due to a reduction in cyclin D1 expression. These effects of 4-NRC also significantly promoted a reduction in mitochondrial activity and membrane depolarization, accumulation of cytosolic cytochrome c and ROS overproduction. Additionally, it triggered an increase in caspases -3/7, -8 and -9 activities. When the cells were pretreated with N-acetyl-l-cysteine ROS scavenger, 4-NRC-induced apoptosis was partially blocked, which suggests that it exerts cytotoxicity though not exclusively through ROS-mediated mechanisms. Discussion and conclusion: 4-NRC has antileukemic properties, inducing apoptosis mediated by mitochondrial-dependent mechanisms with cyclin D1 inhibition. Given that emerging treatment concepts include novel combinations of well-known agents, 4-NRC could offer a promising alternative for chemotherapeutic combinations to maximize tumour suppression.